2000
DOI: 10.1136/sti.76.5.383
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices regarding sexually transmitted infections among general practitioners and medical specialists in Karachi, Pakistan

Abstract: Objectives: To determine the knowledge, attitudes, and practices regarding diagnosis and treatment of sexually transmitted infections (STIs) among specialists-that is, dermatologists, gynaecologists and urologists, and general practitioners (GPs) in Karachi, Pakistan. Methods: Interviewers administered structured questionnaires to doctors conducting outpatient clinics at tertiary hospitals and/or private clinics in Karachi. All private clinics within a 10 km radius of the Aga Khan University, and all tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
1
29
0
3
Order By: Relevance
“…More importantly, no GPs were adequately familiar with associated factors and clinical symptoms of LD (Jawaid et al 2008). Similar studies have assessed the knowledge and skills of GPs in Pakistan and India (Roy et al 2005) regarding common health problems and other disorders including diabetes (Kumar et al 2006a), cancer and palliative care (Shaikh et al 2008), helicobacter pylori infection (Ahmed et al 2009), tuberculosis (Rizvi and Hussain 2001;Shah et al 2003;Shehzadi et al 2005;Vandan et al 2008Vandan et al , 2009, acute respiratory infections (Iqbal et al 1997), acute diarrhea (Patwari et al 1991), malaria (Kamat 2001), sexually transmitted infections (Khandwalla et al 2006), AIDS (Dobe 1995) and preventing tetanus (Dabas et al 2005;Kumar et al 2006b). These studies demonstrate that a high percentage of GPs in Pakistan and India lack sufficient knowledge regarding diagnosis and management of these diseases.…”
mentioning
confidence: 97%
“…More importantly, no GPs were adequately familiar with associated factors and clinical symptoms of LD (Jawaid et al 2008). Similar studies have assessed the knowledge and skills of GPs in Pakistan and India (Roy et al 2005) regarding common health problems and other disorders including diabetes (Kumar et al 2006a), cancer and palliative care (Shaikh et al 2008), helicobacter pylori infection (Ahmed et al 2009), tuberculosis (Rizvi and Hussain 2001;Shah et al 2003;Shehzadi et al 2005;Vandan et al 2008Vandan et al , 2009, acute respiratory infections (Iqbal et al 1997), acute diarrhea (Patwari et al 1991), malaria (Kamat 2001), sexually transmitted infections (Khandwalla et al 2006), AIDS (Dobe 1995) and preventing tetanus (Dabas et al 2005;Kumar et al 2006b). These studies demonstrate that a high percentage of GPs in Pakistan and India lack sufficient knowledge regarding diagnosis and management of these diseases.…”
mentioning
confidence: 97%
“…8 Published studies showed that health care workers are lack of knowledge about diagnosis, the treatment and dental care of HIV/AIDS patients appropriately. 9,10 It was showed that more than half of the medical students thought that treatment of AIDS patients might be dangerous and that their knowledge was not enough to provide dental care effectively. 11 Due to increasing number of HIV/AIDS patients, both dental and medical students must be educated well.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quality of STI case management is often unsatisfactory in low-income countries. 19,20 As yet, to our knowledge, no study on RTI/STI management among health providers has been performed in Laos, but is highly relevant to the nation as a response to the challenges described above.…”
Section: Introductionmentioning
confidence: 89%